Clinical Characteristics and Treatment Outcomes of Growth Hormone Therapy in Pediatric Patients: A Single-Center Experience and Review of Current Literature - Özdemir, Ulaş; Bircan, İffet (Scientific Reports in Medicine, 2025)
Objective: Recombinant human growth hormone (rhGH) became available for clinical trials, and growth hormone deficiency has been treated more safely and effectively since 1985. Growth hormone therapy enables patients to attain an adult height consistent with their genetic target height.The present study was undertaken to evaluate patients’ characteristics, their response to therapy, factors influencing outcome, and side effects of treatment.Method: A retrospective file review was conducted. Out of 149 patients followed up with a GHD diagnosis, 92 patients whose files were accessible and who received treatment for at least 1 year were included in the study. Patients’ chronological ages, ages at diagnosis, sex, pretreatment bone ages (BA), pubertal stages, annual growth velocities, auxological data during treatment, and side effects were recorded.Results: Age at diagnosis, sex, etiologic distributions, and auxological data were found to be similar to the results of Western countries.  Height gain was found to be significant in the first year of treatment, and then growth velocity declined gradually.  Age at the initiation of GH treatment has been shown to be negatively correlated with the response to therapy, emphasizing the need for early diagnosis and treatment of the condition. No significant adverse effects were observed throughout the 16-year follow-up period.Conclusion: Early detection of pathological short stature, particularly Growth Hormone Deficiency (GHD), and the initiation of treatment at an early stage, lead to a superior final height outcome. Patients with GHD can be treated both effectively and safely with recombinant growth hormone therapy